Syndecans - key regulators of cell signaling and biological functions - Afratis, N. A.; Nikitovic, D.; Multhaupt, H. A.; Theocharis, A. D.; Couchman, J. R.; Karamanos, N. K. (FEBS J, 2017)
Syndecans are a small family of four transmembrane proteoglycans in mammals. They have similar structural organization, consisting of an N-terminal ectodomain, single transmembrane domain and C-terminal cytoplasmic domain. Over the years, the association between syndecans and the actin cytoskeleton has been established, which has consequences for the regulation of cell adhesion and migration. Specifically, ecto- and cytoplasmic domains are responsible for the interaction with extracellular matrix molecules and intracellular kinases, respectively. These interactions indicate syndecans as key molecules during cancer initiation and progression. Particularly syndecans interact with other cell surface receptors, such as growth factor receptors and integrins, which lead to activation of downstream signaling pathways, which are critical for the cellular behavior. Moreover, this review describes the key role of syndecans in intracellular calcium regulation and homeostasis. The syndecan-mediated regulation of calcium metabolism is highly correlated with cells' adhesion phenotype through the actin cytoskeleton and formation of junctions, with implications during differentiation and disease progression.
Keywords: *cell adhesion; *growth factor receptors; *growth factors; *integrins; *migration; *Signal Transduction; *signaling; *syndecans; Actin Cytoskeleton/chemistry/metabolism; Animals; Calcium/metabolism; Cell Adhesion; Cell Movement; Extracellular Matrix Proteins/genetics/*metabolism; Extracellular Matrix/chemistry/metabolism; Gene Expression Regulation; homeostasis; Humans; Integrins/genetics/*metabolism; Neoplasms/genetics/*metabolism/pathology; Protein Domains; Protein Kinases/genetics/*metabolism; Receptors, Growth Factor/genetics/*metabolism; Syndecans/genetics/*metabolism